Pregnancy loss, healthy lifestyle behaviours, and long-term risk of hospital-treated infections: a prospective cohort study - Hao Liu; Yan Chen; Han Qu; Zhaochen Sun; Juan Jiang; Yiheng Yin; Yuping Liu; Zhengwei Wan (Reproductive Health, 2026)
Abstract Background Pregnancy loss (PL) is a common reproductive event that may reflect underlying biological vulnerability with potential implications for women’s long-term health. We aimed to investigate the associations of PL and healthy lifestyle with hospital-treated infections and to quantify their combined effects. Methods Using data from 179,971 women in the UK Biobank, Cox proportional hazards regression models were applied to examine the association between the joint effects of PL and the healthy lifestyle index (HLI) and the risk of hospital-treated infections. Results Women with a history of PL had a higher risk of hospital-treated infections in a dose-dependent manner. Specifically, women who experienced two or more PLs had a 23% higher risk of hospital-treated infections (adjusted HR = 1.23, 95% CI: 1.18–1.28), whereas those with a high HLI level had a 31% lower risk (adjusted HR = 0.69, 95% CI: 0.68–0.71). In the joint analysis, compared with women with two or more PLs and a low HLI level, those with no history of PL and a high HLI level had the lowest risk of hospital-treated infections (adjusted HR = 0.56, 95% CI: 0.52–0.60), particularly among participants with low income. No significant additive interaction between PL and HLI was observed after Holm correction; the largest positive departure from additivity was found among women with two or more PLs and a low HLI level (RERI = 0.15, 95% CI: − 0.01 to 0.30; Holm-adjusted P = 0.247). Conclusion PL was associated with a higher long-term risk of hospital-treated infections, while adherence to a healthy lifestyle was associated with a substantially lower risk and partially attenuated the excess infection risk associated with PL, highlighting the potential importance of lifestyle modification for long-term infection risk among women with a history of PL.